Estudio histológico de las glándulas de meibomio en la llama (Lama glama): Histological study of the meibomian glands in the llama (Lama glama) - Ramirez Huanca , Julio Enrique (2023)
The objective of the study was to describe histologically the structural characteristics of the meibomian glands in the llama (Lama glama). These glands are annexed to the eye and contribute to the formation of one of the layers of the tear film responsible for protecting the cornea of the eye. Samples of eyeballs, including eyelids, were collected from five young llamas, from which the meibomian glands were dissected and extracted. The samples were stored in 10% buffered formalin and processed under the paraffin-embedding technique. They were cut, stained and analyzed under the microscope. The glands showed a large number of compound saccular adenomeres, surrounded by connective tissue composed of collagen fibers and blood vessels. Minor and major excretory ducts lined by non-keratinized flat stratified epithelium were observed. The adenomeres showed basal meibocytes that were small and round, central meibocytes of polyhedral shape containing lipid vesicles and superficial meibocytes with pyknotic nuclei, which subsequently disintegrate and show their remains in the lumen of the ducts. Comparison with the literature allows us to conclude that there is a coincidence with other species with respect to the type of adenomer and cell types. Regarding the number of adenomeres, there is similarity with the dromedary camel; in addition, the meibomian glands in llamas are more numerous than in other species and may be an adaptation of this species.